Dreamweaver CS6 for dummies - Warner, Janine 1967- (John Wiley & Sons, 2012)
"Learn to: Design an interactive website with a great user experience; Use CSS3 to transform your designs with drop shadows, rounded corners, and almost any font; Create a site that looks great in all the major web browsers"--Cover.